Hot Mess: Diary of a Wimpy Kid - "Kinney, Jeff" (China; Penguin Books Ltd, 2024)
Get ready for the most hilarious Wimpy Kid book yet! International bestselling author Jeff Kinney serves many laughs in Hot Mess, the 19th book in the Diary of a Wimpy Kid series. Greg Heffley is caught in the middle as the two halves of his extended family come together in a sidesplittingly relatable summer story! Collect all the books in the #1 b[Bokinfo]
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Diary Fiction-English